1998
DOI: 10.1212/wnl.51.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized, placebo-controlled study of oral, high-dose methylprednisolone in attacks of MS

Abstract: Oral high-dose methylprednisolone is recommended for managing attacks of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 9 publications
2
84
0
6
Order By: Relevance
“…In an international optic neuritis study, administration of 1 g/day IV MP for 3 days followed by 21 days of oral MP has been shown to be superior to oral MP administration alone. In another randomized, controlled, prospective study, EDSS scores were shown to significantly improve in steroid-treated groups in the 3 rd and 6 th weeks (67). Two different meta-analyses also reached similar conclusions.…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 65%
“…In an international optic neuritis study, administration of 1 g/day IV MP for 3 days followed by 21 days of oral MP has been shown to be superior to oral MP administration alone. In another randomized, controlled, prospective study, EDSS scores were shown to significantly improve in steroid-treated groups in the 3 rd and 6 th weeks (67). Two different meta-analyses also reached similar conclusions.…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 65%
“…Oral high dose methylprednisolone therapy (500 mg once daily for 5 days followed by a tapering dose over the next 10 days) has recently been shown to significantly accelerate recovery from attacks of relapsing-remitting MS, compared to placebo, 27 The treatment was generally well tolerated, although 38% of patients receiving oral high dose methylprednisolone experienced gastrointestinal symptoms. An earlier study found that oral high dose methylprednisolone therapy (500 mg daily for 5 days) was as effective as the same dose of i.v.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
“…Overall, the four trials of MP (total n = 140) and two trials of ACTH (total n = 237) supported similar benefits of MP and ACTH in acute MS exacerbations [Durelli et al 1985;Filipovic et al 1997;Miller et al 1961;Milligan et al 1987;Rose et al 1970;Sellebjerg et al 1998]. In this review, insomnia was included in the category of psychiatric disturbances.…”
Section: Discussionmentioning
confidence: 87%
“…The available data support an association between corticosteroid treatment and mood disorders as well as other neuropsychiatric disorders such as sleep disturbances, cognitive impairment, and psychosis in some patients [Iacovides and Andreoulakis, 2011;Klein, 1992;Lewis and Smith, 1983;Lienert et al 2013;Martinelli et al 2009;Paparrigopoulos et al 2010;Sellebjerg et al 1998;Sorensen et al 2009;Tsang and Macdonell 2011;Warrington and Bostwick, 2006]. Commonly occurring nonpsychiatric AEs for corticotropin injection are similar to those of corticosteroids, as related to stimulation of cortisol release, and include fluid retention and edema, possible change in glucose tolerance, elevated blood pressure, and increased appetite and weight gain.…”
Section: Introductionmentioning
confidence: 91%